The concept of legal risk in the modern Russian legal order - Suvorov, Ilya Konstantinovich (Юридические исследования, 2025)
The article is devoted to the study of risk as a specific legal category, as well as the historical prerequisites that shaped its content. The author analyzes approaches to understanding legal risk, forms of its normative fixation, and the scope of application of the corresponding provisions of the law. The examination of this institution is conducted in the context of the historical development of ideas about legal risk – from Roman law and pandectism to modern doctrines. Special attention is given to the normative fixation of legal risk in the provisions of the Civil Code of the Russian Federation and its interpretation by the Resolution of the Plenary Supreme Court of the Russian Federation No. 6 of 2020. The research aims to find patterns in the rules for the allocation of risk between the parties to the obligation, criteria for distinguishing the rules about risk and civil liability of the parties to the obligation, as well as to identify the place of legal risk within the system of institutions of Russian obligation law. The methodological foundation of the work consists of historical-legal, comparative-legal, and systemic analysis of the explanations of the Supreme Court of the Russian Federation in connection with the provisions of the Russian Civil Code. The practical significance of this approach lies in clarifying the scope of application of the rules on risk, which allows for a clearer delineation of the zones of responsibility and risk of the parties in such legal relationships. The novelty of the study consists in a comprehensive reconstruction of risk as a purely legal category and the identification of the dual nature of this legal phenomenon specifically in the Russian legal system. As a result, the author demonstrates that in modern Russian law, legal risk functions in two forms – the risk of loss and the risk of not receiving a counter-performance; they are viewed by the legal system as particular cases of the same exception to the general rule concerning the consequences of the accidental occurrence of permanent impossibility of performance of the obligation. The Russian concept of legal risk combines certain features of the traditions initiated by German pandectism and theories of objective civil liability of the 20th century. At the same time, the corresponding legal interpretations maintain the integrity of the conceptual apparatus and internal systemic coherence, which allows risk to be viewed as a phenomenon with a unified legal content. In conclusion, the author formulated the ideas about further development of the doctrine of legal risk in domestic civil law.